Pengaruh Etika Kerja Islam Dan Etika Bisnis Terhadap Komitmen Organisasi Dengan Komitmen Profesi Sebagai Variabel Intervening - Leny Novianti; Hendra Gunawan (Universitas Airlangga, 2010)
This research aims at examining the effect of variable of Islamic work ethics and business ethics on the organizational and professional commitment, in which variable of professional commitment functions as intervening variable. The primary data of this research are collected through collecting opinion or perception of external auditors, who fills in and submit quetionnaire to the researcher. The 30 copies of questionnaire distributed to the public accountant in Riau with sensu. Questionnaire are analyzed by using regression technique with help of SPSS V 16 program and multiple regression analysis. The result of this research shows that the more understand the external auditor the prevailed custom or rule of work, either in the profession ethics or Islamic work ethics and bussiness ethics the better he does his duty and function as external auditor. And furthermore, it has effect on his commitment of profession as a external auditor and commitment of organization.